Prenatal growth stages show the development of the ruminant bony labyrinth and petrosal bone. Issue 2 (11th October 2016) - Costeur, Loïc; Mennecart, Bastien; Müller, Bert; Schulz, Georg
Abstract: Foetuses are a source of scientific information to understand the development and evolution of anatomical structures. The bony labyrinth, surrounding the organ of balance and hearing, is a phylogenetically and ecologically informative structure for which still little concerning growth and shape variability is known in many groups of vertebrates. Except in humans, it is poorly known in many other placentals and its prenatal growth has almost never been studied. Ruminants are a diversified group of placentals and represent an interesting case study to understand the prenatal growth of the ear region. We computed tomography ‐scanned five cow foetuses and an adult petrosal bone ( Bos taurus, Artiodactyla, Mammalia), and describe the bony labyrinth when already ossified. The foetuses encompass the second half of the 9.3‐month‐long gestation period of the cow. They were sampled at different ontogenetic stages to understand how and when the petrosal bone and bony labyrinth ossify in ruminants. The petrosal bone and bony labyrinth ossify within about 20 days in the fourth month of gestation. The bony labyrinth is already fully ossified at least in the 6th month, while only the cochlea, most of the vestibule and the common crus are already ossified at the beginning of the 4th month. The pars canalicularis of the petrosal thus ossifies at last. The size and volume of the bony labyrinth stay similar from the 6th month (possibly even from the 5th). From the end of the 4th month of gestation, a progressive lengthening of the cochlear aqueduct and endolymphatic sac occurs, culminating in the adult form and partly explaining the larger volume of the later. The inner ear in the cow ossifies quickly during the gestation period, being fully ossified around mid‐gestation time, as in humans. The adult size and most of its volume are reached by mid‐gestation time while the petrosal bone and skull still grow. A negative ontogenetic allometry between the bony labyrinth and the petrosal bone and skull is thus observed. It matches the evolutionary negative allometry of the structure observed in earlier studies. Few changes occur after ossification is achieved; only open structures (i.e. cochlear aqueduct and endolymphatic sac) continue to grow after birth and reflect size increase of the petrosal bone.